Numerical taxonomy and virulence screening of aeromonas spp. isolated from healthy and epizootic ulcerative syndrome-positive fishes - Torres, J. L.; Tajima, K.; Mohamed Din, Mohamed Shariff (Asian Fisheries Society, 1993)
Numerical taxonomic analysis was done on 54 previously identified motile Aeromonas spp., including 6 reference strains. At 85% similarity value, 34 of the 54 strains were classified into 8 phenons. When the strains were screened for virulence, phenon I proved to be the most virulent. The majority of isolates in phenon I (highly pathogenic and serologically homogenous A. hydrophia) came from fish exhibiting epizootic ulcerative syndrome (EUS), while those from phenon II (nonpathogenic and serologically heteregenous A. hydrophila) came from healthy fish. Two host species, Channan striata and Clarias sp. from which the greatest diversity of motile aeromonads was recovered, were heavily affected by EUS.